The campus carbon convalescence: creating a carbon-friendly university landscape - Benedick, Jesse Glenn (Kansas State University, 2010)
Universities play a key role in the progression of society. With increased releases of carbon into the atmosphere and the effect of carbon dioxide and related pollutants on air quality and climate, it is critical that universities reduce their carbon footprints. Alternative landscape architectural designs and management techniques, such as rain gardens, constructed wetlands, restored prairies, and woodlands can be implemented to mitigate carbon outputs. Infrastructural landscapes‐called “green infrastructure” for their ability to meet essential human needs using natural processes ‐ sequester carbon at high rates, improve storm water runoff quality, and reduce runoff volumes. Establishment of native and other appropriate green space networks on university campuses can provide rich settings for education, research, and infrastructural services while also promoting carbon neutrality—achieving net zero carbon emissions by balancing carbon released to the atmosphere with an equivalent amount sequestered in vegetation or offset by investing in renewable energy sources. The large experiential landscapes associated with university campuses can operate simultaneously as alternative storm water and carbon mitigating landscapes. They likewise have the potential to restore critical ecological processes while reflecting many of the ecosystems associated with the eco‐region where each university resides. The educational aspect of universities will be enhanced through an interwoven landscape of green infrastructure networks and pedestrian corridors that engage and inform faculty, students, staff and visitors. Development of green infrastructure on university campuses can significantly reduce human impacts on the local environment. They can also increase environmental awareness and showcase responsible stewardship of the land and recourses. These landscapes have great potential to restore native ecosystems and/or historic landscapes habitats. In the right locations they can provide stable environments for various regionally important plant and animal species. Green infrastructure can also reduce short‐ and long‐term costs associated with creating, maintaining, and replacing traditional pipeto‐ pond storm water infrastructure. Increased carbon sequestered in infrastructural landscapes could likewise be a source of additional revenue for universities through the carbon trading market (assuming this market becomes active and remains productive in the U.S.), thus creating a return on investment in the overall green infrastructure system for a campus.
Keywords: Carbon; Campus Design; Landscape Architecture; Kansas State University; Landscape Architecture (0390)